PENEGAKAN HUKUM TERHADAP PERUSAHAAN PINJOLILEGAL BERDASARKAN PUTUSAN KASUS PT BARRACUDA DANPT VEGADATA - Deborah Sondang Romauli (2022)
The phenomenon of illegal fintech in the form of online loans is rampant with various practices that harm consumers because the administrative deductions at the beginning are too large, late fees are also large, the collection method is quite troubling and also profiteering the name of the OJK. The judge's decision in a case is not considered burdensome for business actors who violate the rules even though there are many considerations for the judge. The lack of a legal umbrella that overshadows the problem of this case causes law enforcement and protection to be less than optimal in Indonesia. The research uses a normative juridical approach and research specifications in the form of descriptive analytics. How to collect data through library research and internet media, studying legal materials that are secondary data. With a statutory, conceptual and case study approach. The data analysis technique used is qualitative data analysis. The results of the judge's consideration in a decision are limited to laws and regulations related to the Criminal Code, the Consumer Protection Law and the Trade Law because there is no specific law that can provide criminal sanctions based on perpetrators' violations so that repressive legal protection has not been fulfilled concretely even though the OJK and other institutions have cooperated to make sufficiently good preventive efforts.